Clinical researchBiochemical markers of endothelial dysfunction in pediatric nephrotic syndrome - Shouman, Mohamed; Abdallah, Nagwa; El Tablawy, Nashwa; Rashed, Laila (Archives of Medical Science, 2009)
Introduction: Endothelial dysfunction occurs in many diseases particularly in renal disease. The participation of the different endothelial mediators has been implicated in the pathogenesis of nephrotic syndrome and its complications. The aim of this study was to assess the value of endothelial mediators including nitric oxide (NO) metabolites, cyclic guanosine monophosphate (cGMP), thromboxane A2 (TxA2), and prostacyclin (PGI2) in pediatric patients with nephrotic syndrome at different stages of the disease. Material and methods: Urinary nitrite, serum nitrites and nitrates, as well as serum cGMP, TxA2, and PGI2 were compared between 32 pediatric patients with nephrotic syndrome and 15 controls. Results: Urinary nitrite level was significantly higher among all patient groups compared to controls. However, there were highly significant differences in plasma nitrite and nitrate levels between patient groups and control; plasma nitrite in contrast to plasma nitrate, was significantly higher in children with minimal change glomerulonephritis (MCNS) and non minimal lesion groups than remission group. There was a significant difference between all groups of patients and control as regard cGMP, PGI2 and TxA2. Conclusions: Endothelial dysfunction is related to the activity of the disease and it is reversible. Modulation of endothelial function in NS may offer a novel strategy to reduce progressive renal insult.